The Effect of Winter Lentil (Lens Culinarius L) on the Microbiological Activity of Irrigated Light Sierazem Soils (Texas Journal of Agriculture and Biological Sciences, 2022)
The article describes the role of the winter lentils to increase the fertility of old-irrigated light sierazem soils. When growing winter lentils, the microbiological activity of the studied soils increases markedly compared with the control variant.